1984
DOI: 10.1243/pime_proc_1984_198_113_02
|View full text |Cite
|
Sign up to set email alerts
|

Externally-Pressurized Gas-Lubricated Floating-Ring Porous Journal Bearings: Part 1: Steady State Analysis

Abstract: A new type of gas-lubricatedfloating-ring journal bearing in which thefixed bearing and the ring are both porous, has been conceived and analysed, theoretically, for the steady state Characteristics. Bearing characteristics are presented against two design parameters, namely, clearances ratio and permeability parameter. The comparison of these characteristics with those of externally-pressurized plain porous journal bearings shows that the new bearing represents, with its steady state performance, a distinctly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The authors have also observed that the temperature of the inner film and dissipation of power are considerably higher than those of the outer film, which causes the inner film viscosity to drop more than that of the outer film. Malik 13 has theoretically analysed the gas-lubricated FRB in which bearing housing and the floating ring are both made of porous material. The author has compared the performance of the gas-lubricated FRB with the plain porous journal bearing.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have also observed that the temperature of the inner film and dissipation of power are considerably higher than those of the outer film, which causes the inner film viscosity to drop more than that of the outer film. Malik 13 has theoretically analysed the gas-lubricated FRB in which bearing housing and the floating ring are both made of porous material. The author has compared the performance of the gas-lubricated FRB with the plain porous journal bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Authors have showed that the size of FRB outer clearance is a critical parameter and ring speed ratios can be greatly affected by the onset of nonlinear jumps. Malik 16 has presented the steady-state characteristics of the gas-lubricated FRB in which fixed bearing and the floating ring are both porous. Author has selected the clearance ratio and permeability parameter as the design parameters for the proposed analysis.…”
Section: Introductionmentioning
confidence: 99%